Hematological and hormonal changes associated with acclimatization to moderate altitude
Some basic characteristics of blood were analyzed as part of the previous study (3 weeks at altitude, 3 weeks of re-exposure at sea level). In response to altitude, blood plasma decreased by approximately 20%, causing an increase in hemoglobin and hematocrit measures. The red cell count increased further because of an increase in erythropoietin (EPO) which stimulates the bone marrow to release new red blood cells (reticulocytes). The red cell count remained elevated for the duration of the altitude stay. Upon returning to sea level changes occurred: red cell and reticulocyte counts returned to sea level "normal" values between the fourth and eleventh day; EPO concentrations returned to "normal" within two days; and plasma volumes increased to "normal" levels. Implications: If altitude training is to benefit sea level performances, physiological changes associated with acclimatization should be appropriate for, retained, and present during performance. This did not occur in the course of this study. When athletes competed after three weeks of re-exposure to sea level all altitude changes had disappeared. The exposure in this study was to moderate altitude (2,000 m). The physiological changes were similar to those evidenced when acclimatizing to high altitude (>3,000 m) but the values were lower. This suggests that there are degrees of severity of adaptation to altitude.